Thalamic functional connectivity and its association with behavioral performance in older age. Issue 4 (27th February 2018) - Goldstone, Aimée; Mayhew, Stephen D.; Hale, Joanne R.; Wilson, Rebecca S.; Bagshaw, Andrew P.
Abstract: Introduction: Despite the thalamus' dense connectivity with both cortical and subcortical structures, few studies have specifically investigated how thalamic connectivity changes with age and how such changes are associated with behavior. This study investigated the effect of age on thalamo‐cortical and thalamo‐hippocampal functional connectivity (FC) and the association between thalamic FC and visual–spatial memory and reaction time (RT) performance in older adults. Methods: Resting‐state functional magnetic resonance images were obtained from younger ( n  = 20) and older ( n  = 20) adults. A seed‐based approach was used to assess the FC between the thalamus and (1) sensory resting‐state networks; (2) the hippocampus. Participants also completed visual–spatial memory and RT tasks, from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Results: Older adults exhibited a loss of specificity in the FC between sensory thalamic subregions and corresponding sensory cortex. Greater thalamo‐motor FC in older adults was associated with faster RTs. Furthermore, older adults exhibited greater thalamo‐hippocampal FC compared to younger adults, which was greatest for those with the poorest visual–spatial memory performance. Conclusion: Although older adults exhibited poorer visual–spatial memory and slower reaction times compared to younger adults, "good" and "poorer" older performers exhibited different patterns of thalamo‐cortical and thalamo‐hippocampal FC. These results highlight the potential role of thalamic connectivity in supporting reaction times and memory in aging. Furthermore, these results highlight the importance of including the thalamus in studies of aging to fully understand how brain changes with age may be associated with behavior. Abstract : Thalamo‐hippocampal and thalamo‐sensory cortex functional connectivity (FC) were found to differ between young and older adults. Greatest thalamo‐hippocampal FC was seen in older adults with poorest memory performance, while the greatest thalamo‐sensory cortex FC was identified for older adults with fastest reaction times. These results suggest that differences in thalamic FC with older age are associated with behavioural performance and that these differences can be both detrimental and helpful to performance, depending on the thalamic pathway.